1995
DOI: 10.1055/s-2007-979622
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Aggression and Impulsivity for Self-mutilative Behavior

Abstract: Self-mutilative behavior (SMB) is presented as a specific form of inwardly directed aggressiveness which is thought to be associated with problems of impulse control. Conceptual problems concerning impulsivity and impulsive aggression are discussed. Among different forms of dyscontrolled behavior, SMB is of special heuristic interest because of distinction can be made between patients committing impulsive and those committing premeditated self-harming actions. Psychometric and biological measures of impulsivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 1 publication
0
17
0
3
Order By: Relevance
“…However, researchers have investigated the associations among impulsivity, obsessive compulsive characteristics, and NSSI. Increased impulsivity is associated with history of NSSI (Bennum & Phil, 1983; Herpertz, Sass, & Favazza, 1997), as well as severity of skin picking behaviors (Hayes et al, 2009). Further, individuals with a history of NSSI can be distinguished from non-injurers by the tendency to make rash decisions when faced with negative emotions and by difficulty delaying action in order to plan (Glenn & Klonsky, 2010).…”
Section: Overlapping and Distinctive Features Of Obsessive-compulsivementioning
confidence: 99%
“…However, researchers have investigated the associations among impulsivity, obsessive compulsive characteristics, and NSSI. Increased impulsivity is associated with history of NSSI (Bennum & Phil, 1983; Herpertz, Sass, & Favazza, 1997), as well as severity of skin picking behaviors (Hayes et al, 2009). Further, individuals with a history of NSSI can be distinguished from non-injurers by the tendency to make rash decisions when faced with negative emotions and by difficulty delaying action in order to plan (Glenn & Klonsky, 2010).…”
Section: Overlapping and Distinctive Features Of Obsessive-compulsivementioning
confidence: 99%
“…Clinical experience and some prior research suggest that impulsiveness is an important correlate of NSSI (Herpertz et al, 1997; Herpertz et al, 1995; Simeon et al, 1992). Self-reported impulsiveness is correlated with the severity and frequency of NSSI (Simeon et al, 1992) and with the absence of forethought before engaging in NSSI (Herpertz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported impulsiveness is correlated with the severity and frequency of NSSI (Simeon et al, 1992) and with the absence of forethought before engaging in NSSI (Herpertz et al, 1995). Moreover, the strong link between NSSI and suicide attempts (Joiner, 2006; Nock et al, 2006) combined with research on the role of impulsiveness in suicide attempts (e.g., Dougherty et al, 2004; Jollant et al, 2005) suggest that measures of impulsiveness may provide insight into NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity has been identified as a risk factor for self-harm behaviour [17, 18]. A recent review and meta-analysis across clinical and non-clinical mixed age populations [19] found greater levels of self-reported impulsivity in those who engaged in non-suicidal self-injury compared to those who did not.…”
Section: Introductionmentioning
confidence: 99%